Adaptive Induction of Nonshivering Thermogenesis in Muscle Rather Than Brown Fat Could Counteract Obesity - Bardova, K; Janovska, P; Vavrova, A; Kopecky, J; Zouhar, P (Physiological research, 2024)
Warm-blooded animals such as birds and mammals are able to protect stable body temperature due to various thermogenic mechanisms. These processes can be facultative (occurring only under specific conditions, such as acute cold) and adaptive (adjusting their capacity according to long-term needs). They can represent a substantial part of overall energy expenditure and, therefore, affect energy balance. Classical mechanisms of facultative thermogenesis include shivering of skeletal muscles and (in mammals) non-shivering thermogenesis (NST) in brown adipose tissue (BAT), which depends on uncoupling protein 1 (UCP1). Existence of several alternative thermogenic mechanisms has been suggested. However, their relative contribution to overall heat production and the extent to which they are adaptive and facultative still needs to be better defined. Here we focus on comparison of NST in BAT with thermogenesis in skeletal muscles, including shivering and NST. We present indications that muscle NST may be adaptive but not facultative, unlike UCP1-dependent NST. Due to its slow regulation and low energy efficiency, reflecting in part the anatomical location, induction of muscle NST may counteract development of obesity more effectively than UCP1-dependent thermogenesis in BAT.
Keywords: fyziologická adaptace; kosterní svaly; chvění; energetický metabolismus; Thermogenesis; Animals; Shivering; Adipose Tissue, Brown; Humans; obezita; Obesity; Uncoupling Protein 1; Muscle, Skeletal; zvířata; lidé; Energy Metabolism; hnědá tuková tkáň; uncoupling protein 1; termogeneze; Adaptation, Physiological